Caracterização da caça do município de Governador Dix-Sept Rosado-RN - Dantas, Marcus Arthur Marques (Universidade Federal Rural do Semi-Árido, 2018)
The hunting practice in the city Governador Dix-Sept Rosado – RN was investigated, in between February and March 2018. The city has a territorial area of 1,129,3km², with approximately 13.000 inhabitants. The present research aimed to evaluate the hunting activity through formal and informal interviews (n=17). Among the interviewees, it was verified the hunting with dogs (n=16) is the most practiced, followed by hunting with firearm (n=7). In total, 14 species are object of interest for the hunters, amidst those being six are birds, four are mammals and four reptiles. Among the hunters, 100 % of them affirmed the consumption of the hunted animal’s meat, characterizing the subsistence hunting; Only four of them reported selling the animals meat. Five animals are slaughtered due to representing some type of risk, characterizing control hunt, and three animals were mentioned because of their medicinal properties. The hunters’ preferred animals are the real armadillo, the six-banded armadillo, the skunk, the anteater and the nambu bird. It was also possible to verify the lack of knowledge of the interviewees regarding the risk of zoonoses. Knowing the habits of the hunters is essential to the better control of this activity, in the decision making and elaboration of projects of conservation and management of the local fauna.
Monografia
Keywords: Caçadores; Fauna; Subsistência; Conservação; Hunters; Fauna; Subsistence hunting; Conservation; CIENCIAS AGRARIAS::MEDICINA VETERINARIA